Digitalisasi sistem pelayanan umkm - Narul Huda; Yulisshania Nurfazriyyah; Muhammad Shaddam Albani; Apriyansyah Apriyansyah; Ignatius Joko Dewanto (Journal of Community Service and Empowerment, 2026)
The 3MY Group Community Service Program (KKN) was conducted at Kedai MasGit in Tigaraksa District, Tangerang Regency, as an effort to support the digitalization of service systems for micro, small, and medium enterprises (MSMEs). Problems faced by partners included limited access to menu information, an unstructured ordering process, and the use of a manual service system that could potentially lead to miscommunication and reduce service efficiency. The program involved observation, interviews, SWOT analysis, solution design, implementation, and evaluation. The solution developed included a website landing page integrated with a digital menu, reservation service, and direct access to WhatsApp, along with visuals explaining the ordering process to customers. Implementation results demonstrated that the digital system improved access to information, clarified the ordering process, and supported service efficiency, especially as customer numbers increased. This program contributed to improving service quality and was a strategic step in supporting the digital transformation and operational sustainability of Kedai MasGit.